Inter-discplinary Strategies Involving Nursing, Social Work, Radiology, Physical Therapy, general Practitioners and Emergency Medicine for the Comprehensive Management of Geriatric Patients - Alsubaiei, Muhammed Mutlaq; Alotaibi, Hani Saad Razin; Aljuaid, Fawaz Eid; AlShaabi, Rasheed Hasan; Alenazi, Mashael Fahad Hamoud; Alamri, Fatemah Khaled Mohammed; Alotaibi, Adel Abdullah Gazi; Alhusayni, Abdulwahab Aali; Alenezi, Waad Tamam; Almotairi, Monefah Nawaf; Almutairi, Mona Marzoug; Al-Mutairi, Shaima Marzouq Shaddad (Journal of Posthumanism, 2024)
Background: The increasing complexity of geriatric patients’ health demands coordinated, interdisciplinary strategies that extend beyond traditional siloed approaches. Comprehensive Geriatric Assessment (CGA) and interprofessional collaboration have emerged as effective frameworks for optimizing outcomes across home, community, institutional, and acute care settings.Aim: This review aims to systematically synthesize and map interdisciplinary strategies in geriatric care, focusing on nursing, social work, radiology, physical therapy, primary care, emergency medicine, and public health. Specific objectives were to identify best practices, highlight barriers and facilitators, and propose theoretically anchored frameworks for integrated geriatric management.Methods: A systematic search of PubMed and Google Scholar (2015–2024) was conducted using targeted keywords. Eligible studies included reviews and empirical research addressing interdisciplinary geriatric care. Case reports, duplicates, and incomplete publications were excluded. Extracted evidence was thematically categorized into domains of care delivery and interprofessional collaboration.Results: Findings indicate that CGA-based interventions consistently improve functional outcomes, quality of life, and continuity of care, particularly when nurse-led transitional coordination is emphasized. Home-based interdisciplinary models reduced hospitalizations by up to 27% and improved patient satisfaction. In hospital settings, co-management models lowered morbidity, shortened length of stay, and halved readmission rates. Outpatient and long-term care initiatives enhanced care continuity and relieved burden on family physicians. Simulation-based interprofessional education further strengthened collaboration and discharge planning. However, heterogeneity in team composition, role definitions, and outcome measures remains a challenge.Conclusions: Interdisciplinary strategies centered on CGA and nurse-led coordination significantly improve geriatric care outcomes. Future research should standardize models, refine task distribution, and evaluate cost-effectiveness to enable sustainable system-wide adoption.